Resistive sensor array readout circuit for foot plantar pressure measurement system - Talib, Dayang Nurul Nahar (2017)
Readout circuit is used for interfacing between sensor and digital signal processing unit. It is widely implemented in sensory system to obtain variety of useful information such as pressure and voltage etc. Readout circuit designed for large scale sensor array is important for improving the effectiveness of data acquisition system. However to design such system, many additional components are needed which contributes to complexity and increment of power consumption. This thesis focuses on the design, development and performance study of the readout circuit for large scale sensor array in term of low complexity and high accuracy. The prototype of readout circuit comprises of sensor array, signal acquisition system and graphical user interface. Sensor array has been constructed from 64 FlexiForce pressure sensor to sense pressure values on the foot plantar. Data acquisition system consisting of analogue multiplexer and microcontroller are responsible for selection and digitization of pressure data from the sensor array to the computer to be processed. Then, the processed pressure data is displayed by graphical user interface (GUI) for analysis purpose. A new mathematical equation is also proposed to identify the resistance value on each array. The proposed readout circuit has achieved the objective in terms of low complexity by using microcontroller, multiplexer and standard resistors. While in terms of accuracy, the result obtained from two different evaluations showed satisfactory performance. Results from the first evaluation involving a prototype readout circuit using standard resistors representing resistive type pressure sensor node has resistance value percentage error between 0.04% to 6.5%. Whereas the result obtained from the second evaluation using FlexiForce sensors shows that when pressure is applied on one sensor in each column, the pressure readings of other sensor placed in the same column are also change. The percentage of changes are within the range of 2.14% to 13.46% of the pressure applied onto the sensors. In this research, embedded ADC in PIC microcontroller has been utilised to reduce the complexity, while wireless data transmission has also been implemented in the system for portability.